Chilblains and COVID‐19: why SARS‐CoV‐2 endothelial infection is questioned. Reply from the authors. (20th September 2020) - Colmenero, I.; Santonja, C.; Alonso‐Riaño, M.; Andina, D.; Rodríguez‐Peralto, J.L.; Requena, L.; Torrelo, A.
Abstract : Linked Articles: Baeck et al. Br J Dermatol 2020; 183 :1152–1153 . Colmenero et al. Br J Dermatol 2020; 183 :729–737